Risky Sexual Practices and Associated Factors among Preparatory School Students in Nifas Silk Lafto Sub-City, Addis Ababa, Ethiopia - Chekole, Alemu; Gebrehana, Ewunat; Terefe, Fiseha (Journal of Medical Biomedical and Applied Sciences, 2017)
Background: Increasing premarital sex and its consequences are the issues of global concern and related to broad social, economic and health issues. Because of the risky sexual practice and non-voluntary nature of their sexual activities, adolescents and youths are more likely to contract HIV and other STIs. The objective of this study was to assess the magnitude of Risky Sexual Practices and Associated Factors among Preparatory School.Methods: Cross-sectional school based study was conducted among 1238 preparatory school students in Nifas Silk Lafto sub city in Addis Ababa from November 2012 to April 2013. Multistage cluster sampling method was used. Data were analyzed using univariate, bivariate and multivariate analysis. P-value was used to test the association of independent variables with risky sexual practice.Results:Â  Four hundred twenty six (34.4%) of students reported being engaged in to at least one risky sexual practice related to HIV and other STIs. About 493(39.8%) of respondents reported having previous sexual experience. Of these, 456(92.5%) had sexual intercourse and 309(67.8%) of them had unprotected sex in the past 12 months. Of sexually experienced students, 254(51.5%) of them had multiple sexual partners and 21(4.3%) of them reported ever having sex with commercial sex workers. Out of this, 11(52.4%) had sex with sex workers in the previous 12 months. About 16(3.2%), 20(4.1%) of students reported ever having anal and oral sex. Of these, 10(62.5%) had anal sex and 11(55%) had oral sex in the past 12 months. The result of multivariate analysis showed that Students who drank alcohol (AOR [95% CI] = 13.32 [4.08-43.47]), chewed Khat (AOR [95% CI] = 2.39 [1.34-4.28]) and used substance other than Khat (AOR [95% CI] = 7.17 [4.0-12.86]) were significantly associated with risky sexual practice.Conclusion Significant numbers of students were engaged in risky sexual practice. Strategies and programs should be design targeting factors which exposes school youths to undesirable reproductive health outcomes.